2011
DOI: 10.1143/jjap.50.04dn02
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Catalyst-Free Growth of Silica Nanowires and Carbon Nanotubes Using Ge Nanostructures

Abstract: The use of Ge nanostructures is investigated for the metal-catalyst-free growth of silica nanowires and carbon nanotubes (CNTs). Silica nanowires with diameters of 10-50 nm and lengths of ≤ 1 µm were grown from SiGe islands, Ge dots, and Ge nanoparticles. High-resolution transmission electron microscopy (HRTEM) and energy dispersive X-ray spectroscopy (EDS) reveal that the nanowires grow from oxide nanoparticles on the sample surface. We propose that the growth mechanism is thermal diffusion of oxide through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…This trend is in good agreement with the recent results of Liu et al [11] and Huang et al [12] who reported on CNT growth from oxide nanoparticles. These results suggest the following mechanism for CNT growth [16]. As GeO 2 has a melting point of 400ºC, it is likely that the nanoparticles melt during the pre-anneal at 900ºC, so that CNTs are synthesized from the Ge oxide droplets in which the carbon feedstock is dissolved.…”
Section: Methodsmentioning
confidence: 93%
“…This trend is in good agreement with the recent results of Liu et al [11] and Huang et al [12] who reported on CNT growth from oxide nanoparticles. These results suggest the following mechanism for CNT growth [16]. As GeO 2 has a melting point of 400ºC, it is likely that the nanoparticles melt during the pre-anneal at 900ºC, so that CNTs are synthesized from the Ge oxide droplets in which the carbon feedstock is dissolved.…”
Section: Methodsmentioning
confidence: 93%